Using Web Quests in teaching foreign languages at higher educational institutions - ISHCHUK, Nataliia; GERTSIY, Alexander; LIESOVYI, Volodymyr (Journal of Education, Technology and Computer Science, 2013)
Although one of the education’s major goals is to find efficient ways to integrateweb-based technologies with the traditional teaching methods applied inteaching-learning process, little research has been made in this area. The articleprovides the study of the educational value of Web Quests in teaching foreignlanguages at universities, their role in fostering students’ basic competencies andenhancing their critical thinking. Presented is a Web Quest created by first-yearstudents of Vinnytsia Institute of Economics of Ternopil National EconomicUniversity with its further detailed description. Provided are some results of theexperiment, which prove the didactic efficiency of Web Quests, integrated withother teaching methods, for improving students’ autonomous learning skills.